Iron cluster loaded porous carbon fiber composite material as well as preparation method and application thereof
By preparing iron cluster-loaded porous carbon fiber composite materials, the complexing effect and reaction kinetics of β-cyclodextrin and organic iron salts are used and the electrospinning technology of polysulfide shuttle effect and reaction kinetics in lithium-sulfur batteries are solved, and the application of high-performance lithium-sulfur batteries is realized.
Patent Information
- Application Number
- CN202510863919.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-07-25
- Estimated Expiration
- 2045-06-26
AI Technical Summary
The polysulfide shuttle effect and slow reaction kinetics in lithium-sulfur batteries limit their commercial application. The active sites of existing catalytic materials are prone to failure, making it difficult to achieve high-performance lithium-sulfur batteries.
Iron cluster-loaded porous carbon fiber composite material is used to prepare iron cluster-loaded porous carbon fiber through the complexation of β-cyclodextrin and organic iron salts by electrospinning technology, combining the electron/ion transport capability of porous carbon fibers to coordinate the adsorption of iron clusters and catalytic polysulfide conversion.
It greatly alleviates polysulfide shuttle, improves the electrode conversion reaction kinetics, and realizes a high-performance lithium-sulfur battery with excellent electrocatalytic activity and cycling stability.
Smart Images

Figure CN120376627A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-sulfur battery materials, and particularly relates to an iron cluster-loaded porous carbon fiber composite material, a preparation method thereof, and an application thereof. Background Art
[0002] Lithium-sulfur batteries are considered to be the most promising next-generation high-energy density battery systems due to their advantages such as high energy density (2600 Wh kg -1 )), environmental friendliness, and abundant sulfur reserves. However, the polysulfide shuttle effect and slow reaction kinetics still limit the commercial application of lithium-sulfur batteries. Although researchers have accelerated the conversion of lithium polysulfide by introducing catalytic materials, alleviating the above problems to a certain extent, with the formation of insulating products Li2S / Li2S2, the active sites of the catalytic materials will gradually fail. Therefore, it is particularly important to develop catalysts with abundant active sites.
[0003] Clusters are groups of atoms bound together by well-defined atomicity. Due to their small size (<2 nm), they have abundant active sites. Through cluster catalysis, the inactive parts of nanoparticles can be fully utilized, effectively improving the catalytic efficiency.
[0004] The present invention provides an iron cluster-loaded porous carbon fiber composite material and a preparation method thereof, which synergistically utilize the excellent electron / ion transport ability of porous carbon fiber and the excellent ability of iron clusters to adsorb polysulfides and catalyze their conversion, greatly alleviating the polysulfide shuttle, improving the electrode conversion reaction kinetics, and realizing high-performance lithium-sulfur batteries. Summary of the Invention
[0005] Aiming at the deficiencies of the prior art, the first object of the present invention is to provide a preparation method of an iron cluster-loaded porous carbon fiber composite material. The preparation method of the present invention is scientific, reasonable, easy to implement, and low in cost, and can achieve large-scale production.
[0006] The second object of the present invention is to provide an iron cluster-loaded porous carbon fiber composite material prepared by the above preparation method.
[0007] The third object of the present invention is to provide an application of an iron cluster-loaded porous carbon fiber composite material prepared by the above preparation method. The iron cluster-loaded porous carbon fiber composite material provided by the present invention, through the excellent electron / ion transport ability of porous carbon fiber, synergistically combines with the excellent ability of iron clusters to adsorb polysulfides and catalyze the conversion of polysulfides, greatly alleviating the polysulfide shuttle and improving the electrode conversion reaction kinetics.
[0008] In order to achieve the above objects, the present invention adopts the following technical solutions:
[0009] A preparation method of an iron cluster-loaded porous carbon fiber composite material. β-cyclodextrin and an organic iron salt are added to an organic solvent to obtain a mixed solution A. Polyacrylonitrile is added to the mixed solution A to obtain a mixed solution B. The mixed solution B is electrospun to obtain an organic fiber film, and the organic fiber film is pre-oxidized and calcined in sequence to obtain the composite material.
[0010] In the mixed solution A, the concentration of the organic iron salt is 0.01 - 0.04 mol / L.
[0011] In the preparation method of the present invention, by utilizing the special hollow cylindrical three-dimensional ring structure of β-cyclodextrin and the different hydrophilic and hydrophobic characteristics of the inner and outer surfaces, the hydrophobic organic iron salt is confined in its cavity to form an iron ion inclusion complex. By using the excellent fiber-forming property and structural stability of PAN, an organic fiber membrane is prepared through electrospinning technology. Since β-cyclodextrin and the organic iron salt preferentially form an inclusion complex, it hinders the sublimation of the organic iron salt during the pre-oxidation process. During the subsequent carbonization process, the organic iron is freed from β-cyclodextrin, decomposes and combines with the carbonized fiber to form clusters of 6 - 20 iron atoms anchored on the surface of the carbon fiber.
[0012] Experiments have found that to obtain clusters of iron atoms anchored on the surface of the carbon fiber, first, the mixing order of the raw materials needs to be effectively controlled. Only by mixing β-cyclodextrin and the organic iron salt first can the iron ions be effectively anchored. If directly mixed, it will lead to incomplete anchoring. Second, β-cyclodextrin and the organic iron salt must be used as raw materials. Among them, β-cyclodextrin has both an empty space and hydrophilic and hydrophobic properties, so that the organic iron salt can be confined in its cavity. If β-cyclodextrin is replaced with a substance with only an empty space and no hydrophilic and hydrophobic properties, the organic iron salt cannot be anchored in the empty space. Therefore, if β-cyclodextrin is not added or replaced with others, only single atoms can be loaded in the porous carbon fiber. If an inorganic iron salt is used, it is not conducive to the dispersion of metal atoms and only metal particles can be formed.
[0013] In addition, in the mixed solution A, the molar concentration of the organic iron salt also needs to be effectively controlled. If there is too much organic iron salt, it will exceed the dispersion limit of the carbon fiber, resulting in the inability of iron elements to aggregate in the form of nano-clusters, and only being able to be loaded on the porous carbon fiber composite material in the form of iron metal nanoparticles.
[0014] Preferably, the organic iron salt is selected from at least one of iron acetylacetonate, iron phthalocyanine, ferrocene, and iron porphyrin complex.
[0015] Preferably, the organic solvent is selected from N,N-dimethylformamide.
[0016] Preferably, polyacrylonitrile is added to the mixed solution A and stirred in an oil bath to obtain the mixed solution B. The temperature of the stirring is 40-60 °C, the rate of the stirring is 50-100 r / min, and the time of the stirring is 12-24 h. Through the above process, PAN is uniformly dispersed in the N,N-dimethylformamide solution.
[0017] Preferably, in the mixed solution A, the concentration of β-cyclodextrin is 0.02-0.06 mol / L. The performance is optimal when the molar amount of β-cyclodextrin is controlled within the above range. If there is too much β-cyclodextrin, the spinning solution will become turbid, the viscosity will increase, and it will be difficult to form a uniform spinning solution for subsequent electrospinning. If there is too little β-cyclodextrin, it will be difficult to complex with the organic iron salt, resulting in a large amount of organic iron salt sublimating during the pre-oxidation stage and it will be difficult to form iron clusters during the subsequent carbonization process.
[0018] Preferably, in the mixed solution A, the concentration of the organic iron salt is 0.02-0.04 mol / L, preferably 0.03-0.04 mol / L.
[0019] Preferably, the mass ratio of polyacrylonitrile to β-cyclodextrin is 2-5:1, preferably 2-3:1.
[0020] Preferably, the advancing speed of the electrospinning is 0.5-2 mL / h, and the voltage is 16-24 KV.
[0021] Preferably, the temperature of the pre-oxidation is controlled at 260-300 °C, the heating rate is controlled at 1-5 °C / min, and the time of the pre-oxidation is 2-3 h. Experiments have found that the temperature of the pre-oxidation needs to be controlled within the scope of the present invention. Too high a pre-oxidation temperature will cause the inclusion complex of β-cyclodextrin and the organic iron to decompose and sublimate, and it will be difficult to form iron clusters during the subsequent carbonization process.
[0022] Preferably, the calcination is carried out under an argon protection atmosphere. The temperature of the calcination is 900-1200 °C, and the time of the calcination is 1-4 h.
[0023] After calcination, a membrane-like iron cluster-loaded porous carbon fiber composite material is obtained. In the actual application process, the calcined product is cut into the required size according to the requirements for application.
[0024] The present invention also provides an iron cluster-loaded porous carbon fiber composite material. The iron cluster-loaded porous carbon fiber composite material is composed of porous carbon fibers and iron clusters loaded on the porous carbon fibers. The iron clusters are aggregated in the form of nanoclusters by 6-20 iron atoms.
[0025] Preferably, the iron cluster-loaded porous carbon fiber composite material has the following composition in atomic percentage: N 5% - 10%, Fe 0.1% - 2%, and the balance is C and inevitable impurities.
[0026] Preferably, the iron cluster-loaded porous carbon fiber composite material is in the form of a film.
[0027] Preferably, the fiber diameter of the porous carbon fiber is 50 - 300 nm, the specific surface area is 500 - 1500 m 2 g -1 , and the pore volume is 0.1 - 1 cm 3 g -1 .
[0028] The present invention also provides an application of the iron cluster-loaded porous carbon fiber composite material, using the iron cluster-loaded porous carbon fiber composite material as a sulfur cathode carrier in a lithium-sulfur battery.
[0029] Preferably, the application in the lithium-sulfur battery specifically includes the following steps:
[0030] S1. Dissolve sublimed sulfur in a carbon disulfide solution with a sulfur concentration of 1 - 10 g / mL. Immerse the iron cluster-loaded porous carbon fiber composite material wafer into the carbon disulfide solution for 5 minutes, take it out and put it into a forced-air oven, dry it at 40°C for 12 hours, and then seal the dried sample in an ampoule. Heat it at 155°C for 12 hours in an argon atmosphere to obtain an iron cluster-loaded porous carbon fiber / sulfur cathode sheet;
[0031] S2. Assemble the iron cluster-loaded porous carbon fiber / sulfur cathode sheet, a polypropylene separator, and a lithium metal sheet anode into a lithium-sulfur battery. The dropping amounts of the electrolyte solution (DME / DOL (v / v = 1 / 1) containing 1.0 M LiTFSI and 1 wt% LiNO3) on both sides of the separator are 20 μL on the positive electrode side and 20 μL on the negative electrode side respectively. After the assembled battery is left standing for 6 hours, perform electrochemical tests.
[0032] Compared with the prior art, the beneficial effects of the present invention are:
[0033] 1) In the present invention, the iron cluster-loaded porous carbon fiber composite material, combined with the high sulfur loading brought by the rich pore structure of the carbon fiber and the excellent ability of the iron cluster to adsorb polysulfides and catalyze the conversion of polysulfides, greatly alleviates the polysulfide shuttle, improves the electrode conversion reaction kinetics, realizes a high-performance lithium-sulfur battery, and has application prospects.
[0034] 2) The preparation method of the iron cluster-loaded porous carbon fiber composite material in the present invention utilizes the special hollow cylindrical three-dimensional ring structure of β-cyclodextrin and the different hydrophilic and hydrophobic characteristics of the inner and outer surfaces to confine the hydrophobic organic iron salt in its cavity, and combines the electrospinning technology to prepare the iron cluster-loaded porous carbon fiber composite material. The preparation method is scientific, reasonable, easy to implement, and low in cost, and can achieve large-scale production.
[0035] 3) The iron cluster-loaded porous carbon fiber composite material prepared in the present invention, as a cathode carrier material for lithium-sulfur batteries, has excellent electrocatalytic activity. The battery prepared with this material has a maximum discharge specific capacity of 1097 mAh / g at a discharge rate of 0.2C, and the capacity can still remain at 995 mAh / g after 100 cycles. Brief Description of the Drawings
[0036] Figure 1 It is the transmission electron microscope (TEM) image of the iron cluster-loaded porous carbon fiber composite material prepared in Example 1 of the present invention.
[0037] Figure 2 It is the TEM image and high-resolution TEM image of the iron single crystal-loaded porous carbon fiber composite material prepared in Comparative Example 1 of the present invention, where Figure 2 (a) is the TEM image, Figure 2 (b) is the high-resolution TEM image.
[0038] Figure 3 It is the TEM image and high-resolution TEM image of the iron single crystal-loaded porous carbon fiber composite material prepared in Comparative Example 2 of the present invention, where Figure 3 (a) is the TEM image, Figure 3 (b) is the high-resolution TEM image.
[0039] Figure 4 It is the aberration-corrected scanning transmission electron microscope (AC-STEM) image of the iron cluster-loaded porous carbon fiber composite material prepared in Example 1 of the present invention.
[0040] Figure 5 It is the AC-STEM image of the sample prepared in Comparative Example 3 of the present invention.
[0041] Figure 6 It is the X-ray crystal diffraction (XRD) image of the samples prepared in Example 1 and Comparative Example 1 of the present invention.
[0042] Figure 7 It is the cycle performance image of the battery prepared in Example 1 of the present invention under the condition of a discharge rate of 0.2C.
[0043] Figure 8Cycling performance graph of the battery prepared in Comparative Example 1 of the present invention under the condition of 0.2C discharge rate.
[0044] Figure 9 Cycling performance graph of the battery prepared in Comparative Example 2 of the present invention under the condition of 0.2C discharge rate.
[0045] Figure 10 Cycling performance graph of the battery prepared in Comparative Example 3 of the present invention under the condition of 0.2C discharge rate. Detailed implementation manners
[0046] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0047] Example 1
[0048] Preparation method of iron cluster-loaded porous carbon fiber composite material, specifically carried out according to the following steps:
[0049] 1) Add 0.454 g of β-cyclodextrin, 0.074 g of ferrocene and 10 mL of N,N-dimethylformamide into a 25 mL beaker, place it on a stirrer, and stir at 50-100 r / min for 1 h to obtain solution A;
[0050] 2) Add 1.2 g of polyacrylonitrile into the mixed solution A, stir in an oil bath, the stirring temperature is 40 °C, the stirring rate is 100 r / min, and the stirring time is 20 h to obtain mixed solution B;
[0051] 3) Use electrospinning technology to spin the mixed solution B prepared in step 3, with the conditions of a propulsion speed of 0.5 mL / h and a voltage of 16 KV;
[0052] 4) Pre-oxidize the electrospun organic fiber film, the pre-oxidation temperature is 280 °C, the heating rate is 5 °C / min, and the pre-oxidation time is 2 h;
[0053] 5) Calcinate the pre-oxidized film prepared in step 4 at 1000 °C for 2 h under an argon protection atmosphere to obtain an iron cluster-loaded porous carbon fiber composite material. Analyze and characterize its morphology and structure, as shown in Figure 1 、 4 、6.
[0054] Figure 1This is the TEM image of the iron cluster-loaded porous carbon fiber composite material. It can be seen from the figure that the iron cluster-loaded porous carbon fiber composite material presents a fibrous structure with a fiber diameter of 50 to 200 nm.
[0055] Figure 4 This is the AC-STEM image of the iron cluster-loaded porous carbon fiber composite material. Using a higher magnification, we can clearly see that the iron clusters composed of 6-20 iron atoms aggregated in the form of nanoclusters are loaded on the porous carbon fiber. At the same time, no lattice fringes representing the crystal structure were found, indicating that the main body of the sample is amorphous carbon loaded with Fe clusters.
[0056] Figure 6 The upper curve is the XRD diagram of the porous carbon fiber composite material loaded with iron clusters in Example 1. A hump can be observed at about 21°, corresponding to the (002) crystal plane of graphite. The diffraction peak is relatively broad, indicating a high degree of disorder. No diffraction peaks of iron element and its compounds were observed in the figure, indicating that the iron clusters in the present invention are clusters formed by iron atoms, have no metallic properties, and are not iron metal clusters, further illustrating the successful preparation of the porous carbon fiber composite material loaded with iron clusters.
[0057] The iron cluster-loaded porous carbon fiber composite material prepared above is applied in a lithium-sulfur battery, specifically according to the following steps:
[0058] 1) Cut the iron cluster-loaded porous carbon fiber membrane into discs with a diameter of 10 mm for later use, dissolve the sublimated sulfur in a carbon disulfide solution, the sulfur concentration is 10 g / mL, immerse the iron cluster-loaded porous carbon fiber composite disc in the carbon disulfide solution for 5 minutes, take it out and put it in a blast oven, dry it at 40°C for 12 hours in an argon atmosphere, and put the dried sample into an ampoule and seal it. Heat it at 155°C for 12 hours in an argon atmosphere to obtain an iron cluster-loaded porous carbon fiber / sulfur positive electrode sheet.
[0059] 2) In an anhydrous and oxygen-free glove box, the prepared iron cluster-loaded porous carbon fiber / sulfur cathode sheet was placed in the center of the cathode shell, 20 μL of electrolyte (DME / DOL (v / v = 1 / 1) containing 1.0 M LiTFSI and 1 wt% LiNO3) was added, and a 19 mm diameter polypropylene diaphragm was placed. 10 μL of the above electrolyte was added, and then a 15 mm diameter metal lithium sheet was placed. After adding a gasket and a shrapnel, the anode shell was covered and assembled into a lithium-sulfur battery after hydraulic pressure. The assembled battery was left to stand for 6 h before electrochemical testing. The test results are shown in Figure 7 shown.
[0060] Figure 7This is the cycling performance graph of the prepared battery under the condition of 0.2C discharge rate. It can be seen from the graph that under the condition of 0.2C discharge rate, the initial discharge specific capacity of the battery is 1097 mAh / g. After 100 cycles, it still has a discharge specific capacity of 995 mAh / g, and the capacity retention rate is 90.7%. Its excellent cycling stability is inseparable from the strong adsorption and efficient conversion of polysulfides by Fe clusters and the excellent electron / ion conduction performance of porous carbon fibers.
[0061] Example 2:
[0062] A preparation method of iron cluster-loaded porous carbon fiber composite material is specifically carried out according to the following steps:
[0063] 1) Add 0.454 g of β-cyclodextrin, 0.06 g of iron phthalocyanine and 10 mL of N,N-dimethylformamide into a 25 mL beaker, place it on a stirrer, and stir at 50 - 100 r / min for 1 h to obtain solution A;
[0064] 2) Add 1.0 g of polyacrylonitrile into the mixed solution A, stir in an oil bath, the stirring temperature is 40 °C, the stirring rate is 100 r / min, and the stirring time is 24 h to obtain mixed solution B;
[0065] 3) Use electrospinning technology to spin the mixed solution B prepared in step 3, with the conditions of a feeding speed of 0.5 mL / h and a voltage of 20 KV;
[0066] 4) Pre-oxidize the electrospun organic fiber film, the pre-oxidation temperature is 280 °C, the heating rate is 5 °C / min, and the pre-oxidation time is 2 h;
[0067] 5) Calcinate the pre-oxidized film prepared in step 4 at 1000 °C for 2 h under the atmosphere of argon protection to obtain the iron cluster-loaded porous carbon fiber composite material.
[0068] Apply the above-prepared iron cluster-loaded porous carbon fiber composite material in a lithium-sulfur battery, and the steps are the same as those in Example 1. The battery prepared with the iron cluster-loaded porous carbon fiber composite material obtained in Example 2 as the sulfur carrier has an initial discharge specific capacity of 1146 mAh / g under the condition of 0.2C discharge rate. After 100 cycles, it has a discharge specific capacity of 930 mAh / g, and the capacity retention rate is 81.2%.
[0069] Example 3:
[0070] A preparation method of iron cluster-loaded porous carbon fiber composite material is specifically carried out according to the following steps:
[0071] 1) Add 0.454 g of β-cyclodextrin, 0.037 g of ferrocene and 10 mL of N,N-dimethylformamide into a 25 mL beaker, place it on a stirrer, and stir at 50 - 100 r / min for 1 h to obtain solution A;
[0072] 2) Add 1.0 g of polyacrylonitrile into the mixed solution A, stir in an oil bath, with the stirring temperature at 40 °C, the stirring rate at 100 r / min, and the stirring time at 24 h to obtain mixed solution B;
[0073] 3) Use electrospinning technology to spin the mixed solution B prepared in step 3, with the conditions of a propulsion speed of 0.5 mL / h and a voltage of 20 KV;
[0074] 4) Pre-oxidize the electrospun organic fiber film, with the pre-oxidation temperature at 280 °C, the heating rate at 5 °C / min, and the pre-oxidation time at 2 h;
[0075] 5) Calcinate the pre-oxidized film prepared in step 4 at 1000 °C for 2 h under an argon protection atmosphere to obtain an iron cluster-loaded porous carbon fiber composite.
[0076] Apply the above-prepared iron cluster-loaded porous carbon fiber composite in a lithium-sulfur battery, and the steps are the same as in Example 1. The battery prepared with the iron cluster-loaded porous carbon fiber composite obtained in Example 3 as the sulfur carrier has an initial discharge specific capacity of 1139 mAh / g under the condition of a 0.2C discharge rate. After 100 cycles, it has a discharge specific capacity of 943 mAh / g, and the capacity retention rate is 82.8%.
[0077] Comparative Example 1:
[0078] Other conditions are the same as in Example 1, only replacing the organic iron salt with ferric nitrate. The specific steps are as follows:
[0079] 1) Add 0.454 g of β-cyclodextrin, 0.097 g of ferric nitrate and 10 mL of N,N-dimethylformamide into a 25 mL beaker, place it on a stirrer, and stir at 50 - 100 r / min for 1 h to obtain solution A;
[0080] 2) Add 1.2 g of polyacrylonitrile into the mixed solution A, stir in an oil bath, with the stirring temperature at 40 °C, the stirring rate at 100 r / min, and the stirring time at 20 h to obtain mixed solution B;
[0081] 3) Use electrospinning technology to spin the mixed solution B prepared in step 3, with the conditions of a propulsion speed of 0.5 mL / h and a voltage of 16 KV;
[0082] 4) Pre-oxidizing the spun organic fiber film at a temperature of 280°C, a heating rate of 5°C / min, and a pre-oxidation time of 2 h;
[0083] 5) The pre-oxidized film prepared in step 4 was calcined at 1000°C for 2 h in an argon atmosphere to obtain an iron metal nanoparticle-loaded porous carbon fiber composite material. The morphology and structure were analyzed and characterized, such as Figure 2 , 6 shown.
[0084] Figure 2 (a) is a TEM image of the iron metal nanoparticle-loaded porous carbon fiber composite material prepared in Comparative Example 1, and Figure 1 The magnification is the same as that of the figure. It can be seen from the figure that the iron metal nanoparticle-loaded porous carbon fiber composite material presents a fibrous structure with a fiber diameter of 50 to 200 nm. In addition, it can be seen that metal nanoparticles of different sizes are scattered on the carbon fiber. The size of the metal nanoparticle agglomerates is much larger than the size of the iron clusters provided in the embodiment of the present invention. High-resolution analysis of these nanoparticles, such as Figure 2 As shown in (b), the interplanar spacing of the nanoparticles is 0.349 nm, corresponding to the (200) crystal plane of elemental iron.
[0085] Figure 6 The curve below is the XRD pattern of the porous carbon fiber composite material loaded with iron metal nanoparticles prepared in Comparative Example 1. A hump can be observed at about 26°, corresponding to the (111) crystal plane of carbon. The diffraction peak is relatively broad, indicating a high degree of disorder. In addition, a sharp diffraction peak is observed at about 44.7°, corresponding to the (110) crystal plane of Fe element. XRD and TEM analysis show that during the carbonization process, inorganic metal salts such as iron nitrate are not conducive to the dispersion of metal atoms, and are prone to induce metal agglomeration to form iron metal nanoparticles.
[0086] The iron metal nanoparticle-loaded porous carbon fiber composite material prepared above is used in a lithium-sulfur battery, and the steps are the same as those in Example 1.
[0087] Figure 8 The figure is a cycle performance diagram of the prepared battery under the condition of 0.2C discharge rate. It can be seen from the figure that the battery prepared by using the iron metal nanoparticle-loaded porous carbon fiber composite material as a sulfur carrier in Comparative Example 1 has an initial discharge capacity of 1005 mAh / g under the condition of 0.2C discharge rate, and has a discharge capacity of 792 mAh / g after 100 cycles, and a capacity retention rate of 78.8%. The initial discharge capacity and cycle stability of the battery are much lower than those in Example 1, indicating that it is difficult to achieve efficient utilization of catalysts with iron metal nanoparticles.
[0088] Comparative Example 2:
[0089] Other conditions were the same as those in Example 1, except for the addition amount of ferrocene: The specific steps were as follows:
[0090] 1) Add 0.454 g of β-cyclodextrin, 0.12 g of ferrocene and 10 mL of N,N-dimethylformamide into a 25 mL beaker, place it on a stirrer, and stir at 50 - 100 r / min for 1 h to obtain Solution A;
[0091] 2) Add 1.2 g of polyacrylonitrile into the mixed Solution A, stir in an oil bath, the stirring temperature is 40 °C, the stirring rate is 100 r / min, and the stirring time is 20 h to obtain mixed Solution B;
[0092] 3) Use electrospinning technology to spin the mixed Solution B prepared in step 3, with the conditions of a pushing speed of 0.5 mL / h and a voltage of 16 KV;
[0093] 4) Pre-oxidize the electrospun organic fiber film, the pre-oxidation temperature is 280 °C, the heating rate is 5 °C / min, and the pre-oxidation time is 2 h;
[0094] 5) Calcinate the pre-oxidized film prepared in step 4 at 1000 °C for 2 h under the atmosphere of argon protection to obtain a porous carbon fiber composite loaded with iron metal nanoparticles. Analyze and characterize its morphology and structure, as Figure 3 .
[0095] Figure 3 (a) is the TEM image of the porous carbon fiber composite loaded with iron metal nanoparticles prepared in Comparative Example 2. It can be seen from the figure that the porous carbon fiber composite loaded with iron metal nanoparticles presents a fibrous structure, and the fiber diameter is about 100 nm. In addition, it can be seen that the metal nanoparticles are uniform and evenly distributed on the carbon fiber. Perform high-resolution analysis on these nanoparticles, as Figure 3 (b) shows that the crystal plane spacing of the nanoparticles is 0.349 nm, corresponding to the (200) crystal plane of elemental iron. This analysis shows that it is difficult for excessive organometallic salts to be evenly dispersed during the carbonization process, and iron atoms exist in the form of metal. Only the content of organic iron salt in the preparation method of the present invention can form iron clusters.
[0096] Apply the prepared porous carbon fiber composite loaded with iron metal nanoparticles in a lithium-sulfur battery, and the steps are the same as those in Example 1.
[0097] Figure 9It is the cycle performance graph of the prepared battery under the condition of 0.2C discharge rate. It can be seen from the graph that for the battery prepared with the iron metal nanoparticle-loaded porous carbon fiber composite as the sulfur carrier, under the condition of 0.2C discharge rate, the initial discharge specific capacity is 1063 mAh / g. After 100 cycles, it has a discharge specific capacity of 862 mAh / g, and the capacity retention rate is 81.1%. The initial discharge specific capacity of this battery is the same as that of Example 1, but its cycle stability is much lower than that of Example 1, indicating that it is difficult to achieve efficient utilization of the catalyst with iron metal nanoparticles.
[0098] Comparative Example 3:
[0099] Other conditions are the same as those in Example 1, except that β-cyclodextrin is not added. The specific steps are as follows:
[0100] 1) Add 0.12 g of ferrocene and 10 mL of N,N-dimethylformamide into a 25 mL beaker, place it on a stirrer, and stir at 50 - 100 r / min for 1 h to obtain Solution A;
[0101] 2) Add 1.2 g of polyacrylonitrile into the mixed Solution A, stir in an oil bath, with a stirring temperature of 40 °C, a stirring rate of 100 r / min, and a stirring time of 20 h to obtain mixed Solution B;
[0102] 3) Use electrospinning technology to spin the mixed Solution B prepared in step 3, with a feeding rate of 0.5 mL / h and a voltage of 16 KV;
[0103] 4) Pre-oxidize the electrospun organic fiber film, with a pre-oxidation temperature of 280 °C, a heating rate of 5 °C / min, and a pre-oxidation time of 2 h;
[0104] 5) Calcinate the pre-oxidized film prepared in step 4 at 1000 °C for 2 h under an argon protection atmosphere to obtain an iron single-atom-loaded porous carbon fiber composite. Analyze and characterize its morphology and structure, as Figure 5 .
[0105] Figure 5 It is the AC-TEM graph of the iron single-atom-loaded porous carbon fiber composite. It can be seen from the graph that iron elements are loaded in the porous carbon fiber in the form of single atoms. This analysis shows the necessity of β-cyclodextrin for the formation of iron clusters. Through the inclusion effect of the organic iron salt, several iron ions aggregate in the cavity of β-cyclodextrin, and through carbonization, iron clusters are prepared. Without β-cyclodextrin, iron elements can only exist in the form of single atoms.
[0106] Apply the material prepared above in a lithium-sulfur battery, and the steps are the same as those in Example 1.
[0107] Figure 10 This is the cycling performance graph of the prepared battery at a discharge rate of 0.2C. It can be seen from the graph that for the battery prepared with the single-atom iron-loaded porous carbon fiber composite as the sulfur carrier, at a discharge rate of 0.2C, the initial discharge specific capacity is 1060 mAh / g. After 100 cycles, the discharge specific capacity is 840 mAh / g, and the capacity retention rate is 79.2%. The initial discharge specific capacity and cycling stability of this battery are much lower than those in Example 1, indicating that it is difficult for single-atom iron to achieve efficient utilization of the catalyst, and its cycling performance is poor.
[0108] In summary, combining Examples 1-3 and Comparative Examples 1-3, the following analysis can be obtained:
[0109] In Examples 1-3, the organic iron salt is ferrocene or iron phthalocyanine, and the content of the organic iron salt is adjusted. It can be seen that the selected organic iron salts in the present invention can all form inclusion compounds with β-cyclodextrin using their hydrophobic properties, and form iron clusters through carbonization, thereby preparing an iron-cluster-loaded porous carbon fiber composite;
[0110] In Comparative Example 1, the selection of the organic iron salt is adjusted. It can be seen that the selection of the iron salt affects the preparation of the iron-cluster-loaded porous carbon fiber composite. β-cyclodextrin cannot produce an inclusion effect on hydrophilic iron nitrate, and iron elements are prone to aggregation during carbonization, forming iron metal nanoparticles. When the iron metal nanoparticle-loaded porous carbon fiber composite is applied to a lithium-sulfur battery, the initial discharge specific capacity and cycling stability of the battery are much lower than those of the lithium-sulfur battery applied with the iron-cluster-loaded porous carbon fiber composite.
[0111] In Comparative Example 2, the content of the organic iron salt is adjusted. It can be seen that the content of the organic iron salt affects the preparation of the iron-cluster-loaded porous carbon fiber composite. The ability of carbon fiber to load iron clusters is limited. Excessive organic salts exceed the dispersion limit of carbon fiber, resulting in the inability of iron elements to aggregate in the form of nanoclusters, and only an iron metal nanoparticle-loaded porous carbon fiber composite can be obtained.
[0112] In Comparative Example 3, the application of β-cyclodextrin is adjusted. It can be seen the necessity of β-cyclodextrin in cluster formation. The present invention utilizes the inclusion effect of β-cyclodextrin on the organic iron salt to enrich organic iron ions in its cavity and form clusters after carbonization. Without adding β-cyclodextrin, only a single-atom-loaded porous carbon fiber composite can be obtained. When the single-atom iron-loaded porous carbon fiber material is applied to a lithium-sulfur battery, the initial discharge capacity of the battery is relatively high, but its cycling stability is poor, much lower than that of the lithium-sulfur battery applied with the iron-cluster-loaded porous carbon fiber composite.
[0113] In summary, in the preparation method of the present invention, by utilizing the special hollow cylindrical three-dimensional ring structure of β-cyclodextrin and the different hydrophilic and hydrophobic properties inside and outside, the hydrophobic organic iron ions are confined in its cavity, and combined with the electrospinning technology, a composite material of iron clusters loaded on porous carbon fibers is prepared. The composite material of iron clusters loaded on porous carbon fibers has iron clusters in which iron atoms are aggregated in the form of nanoclusters, which synergistically bring high sulfur loading with the rich pore structure of carbon fibers, and the excellent ability of iron clusters to adsorb polysulfides and catalyze the conversion of polysulfides, greatly alleviating the polysulfide shuttle, improving the reaction kinetics of electrode conversion, and realizing high-performance lithium-sulfur batteries.
[0114] As mentioned above, it is only used to help understand the method of the present invention and its core essence, but the protection scope of the present invention is not limited thereto. For those of ordinary skill in the art within the technical scope disclosed by the present invention, any equivalent substitution or change made according to the technical solution and inventive concept of the present invention should be covered within the protection scope of the present invention. In summary, the content of this specification should not be construed as a limitation to the present invention.
Claims
1. A preparation method of an iron cluster-loaded porous carbon fiber composite material, characterized in that: β-cyclodextrin and an organic iron salt are added to an organic solvent to obtain a mixed solution A. Polyacrylonitrile is added to the mixed solution A to obtain a mixed solution B. The mixed solution B is electrospun to obtain an organic fiber film, and the organic fiber film is pre-oxidized and calcined in sequence to obtain the product. In the mixed solution A, the concentration of the organic iron salt is 0.01 - 0.04 mol / L.
2. The preparation method of an iron cluster-loaded porous carbon fiber composite material according to claim 1, wherein: The organic iron salt is selected from at least one of iron acetylacetonate, iron phthalocyanine, ferrocene, and iron porphyrin complex. The organic solvent is selected from N,N-dimethylformamide.
3. The preparation method of an iron cluster-loaded porous carbon fiber composite material according to claim 1, characterized in that: Polyacrylonitrile is added to the mixed solution A and stirred in an oil bath to obtain a mixed solution B. The temperature of the stirring is 40 - 60 °C, the rate of the stirring is 50 - 100 r / min, and the time of the stirring is 12 - 24 h.
4. The preparation method of an iron cluster-loaded porous carbon fiber composite material according to claim 1, wherein: In the mixed solution A, the concentration of β-cyclodextrin is 0.02 - 0.06 mol / L. The mass ratio of polyacrylonitrile to β-cyclodextrin is 2 - 5:
1.
5. The preparation method of an iron cluster-loaded porous carbon fiber composite material according to claim 1, characterized in that: The advancing speed of the electrospinning is 0.5 - 2 mL / h, and the voltage is 16 - 24 KV.
6. The preparation method of an iron cluster-loaded porous carbon fiber composite material according to claim 1, characterized in that: The temperature of the pre-oxidation is controlled at 260 - 300 °C, the heating rate is controlled at 1 - 5 °C / min, and the time of the pre-oxidation is 2 - 3 h.
7. The preparation method of an iron cluster-loaded porous carbon fiber composite material according to claim 1, wherein: The calcination is carried out under an argon protection atmosphere. The temperature of the calcination is 900 - 1200 °C, and the time of the calcination is 1 - 4 h.
8. A porous carbon fiber composite material loaded with iron clusters prepared by the preparation method according to any one of claims 1-7, characterized in that: The iron cluster-loaded porous carbon fiber composite material consists of porous carbon fibers and iron clusters loaded on the porous carbon fibers. The iron clusters are aggregated in the form of nanoclusters by 6 - 20 iron atoms.
9. The iron cluster-supported porous carbon fiber composite material according to claim 8, wherein: For the iron cluster-loaded porous carbon fiber composite material, calculated by atomic percentage, the composition is as follows: N 5% - 10%, Fe 0.1% - 2%, and the balance is C and inevitable impurities. The iron cluster-loaded porous carbon fiber composite material is in the form of a film. The fiber diameter of the porous carbon fiber is 50~300 nm, the specific surface area is 500~1500 m 2 g -1 , and the pore volume is 0.1~1 cm 3 g -1 .
10. Use of an iron cluster-supported porous carbon fiber composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The iron cluster-loaded porous carbon fiber composite material is used as a sulfur cathode carrier in a lithium-sulfur battery.
Citation Information
Patent Citations
Porous carbon nanofiber and preparation method thereof and lithium-sulfur battery
CN110158200A
Preparation method and application method of self-supporting cathode with lithium ion conductivity
CN110690462A
Preparation method and application of cathode material sourced from ferrocene
CN110711580A
Cyclodextrin-based transition metal monatomic catalytic material and preparation method thereof
CN110801863A
Fe3O4 / porous carbon nanofibers as well as preparation method and application thereof
CN112279304A